Capillary rise on rounded polygon corners of pillar and array structures - Ha, Jonghyun; Park, Keunhwan; Jung, Wonjong (Physics of Fluids, 2024)
Capillary rise, where liquid climbs narrow spaces against gravity, plays an important role in both natural and technological processes. This study investigates capillary wetting in rounded polygon corners, a less-studied area in microfluid mechanics with significant implications for industries such as nanotextured surface cleaning, micro-soldering, food technology, and water harvesting. Through experimental analysis, we examine the relationship between capillary rise height and the geometric parameters of curvature radius and angle in rounded polygonal pillar and array structures. Our findings reveal a direct correlation where the capillary rise height increases as the radius of the corner increases, emphasizing the critical role of corner geometry in enhancing capillary action. This research not only deepens understanding of capillary behavior in complex geometries but also provides valuable insights for optimizing capillary-based applications across. By considering the influence of geometric complexity on capillarity, our study paves the way for innovative approaches in the design and development of efficient systems for fluid manipulation and control.
Keywords: Array structures; Capillary rise; Capillary wetting; Micro-fluid; Nanotextured surface; Narrow spaces; Natural process; Pillar structure; Polygon corners; Technological process